Microcontroller-Based Smart Locker Prototype - Tinambunan, Delila Agustin; Sukardi, Sukardi (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This research aims to design and build a prototype smart locker based on ESP32 microcontroller as a security solution that is more efficient and reliable than conventional systems. This system utilizes remote technology by using ESP32 connected via WiFi, to remotely control and monitor the locker. The smart locker is equipped with a vibration sensor that is able to detect forced opening attempts and generate an alarm as an additional form of security. Tests were conducted to ensure the reliability of the system under different operational conditions, including a range test between the transmitter and receiver up to a distance of 60 meters. The test results show that the smart locker system functions well in accordance with the design, without any loss of connection during the control process. With this technology, it is expected to be applied in various places that require high security smart locker systems, such as libraries and other public facilities. This research provides suggestions for further development, including improved microcontroller specifications and integration with a web-based monitoring system for more efficient administration.